94.2k views
16 votes
-1/3x-4/3y=-2 1/3x-2/3y=4 using elimination

1 Answer

6 votes

-1/3x-4/3y=2

1/3x-2/3y=4

First realize that the coefficient of x is -1/3 and 1/3 which can be eliminated with addition

Adding the two equations together gets

-6/3y=6

Simplify

-2y=6

y=-3

Substitute back into original equation

1/3x-2/3(-3)=4

1/3x+2=4

1/3x=2

x=6

Answer

x=6, y=-3

Check answer

-1/3(6)-4/3(-3) =?= 2

-2+4=2

2=2

Done!

User Oleksii Polivanyi
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.